The Royal Marines Capture, Fortification and Defence of Anholt Island 1807–1812. Issue 4 (2nd October 2019) - Robson, Martin L.
Abstract : During the British gunboat war against Denmark–Norway in the period 1808–13, the Danish island of Anholt posed a navigational hazard to Baltic convoys carrying strategic materials and manufactured goods through the Baltic. It also offered a secure supply of freshwater and an alternative anchorage to Wingo Sound. When the lighthouse marking the island and its reefs was extinguished, a Royal Navy invasion force of marines and seamen captured the island and, with the assistance of the inhabitants, subsequently fortified the structure and adjacent land. Thereafter light vessels operating from the island carried supplies from Sweden and conducted commerce raiding. On the subsequent attempt to recapture the island in March 1811, Danish forces, including oared gunboats, were repulsed by the Royal Marines using artillery in prepared positions, and warships that were sent following intelligence of the attack.